(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This paper studies more important reforms in employment contracts after Law3/2012. The main goal of the Labour Reform is helping to create employment but with out giving up quality and stability. However, the measures are inconsistent with this purpose since economic crisis have significantly conditioned Government decisions. As a result of that, there are doubts about effectiveness of the reform and itsability to create jobs.